Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

5x + 3y = 6
-3x - 3y = 6


Sagot :

Answer:

(x,y)=(6,-8)

x=6, y=-8

Step-by-step explanation:

There are many was to answer this question, some are substitution and elimination. I am going to use the substitution method.  

Your system of equation is 5x+3y=6 and -3x-3y=6

5x+3y=6

-5x  -5x

3y=6-5x

Now you substittion the first equation to the sencond one. It will look like:

-3x-(6-5x)=6

-3x-6+5x=6

2x-6=6

+6    +6

2x=12

Divide both sides by 2 and you get

x=6

Now lets substiton x inot the orgianl equation.

-3(6)-3y=6

-18-3y=6

+18    +18

-3y=24

Divide both sides by -3

y=-8

So, the answer is x=6, y=-8